Characterization of Moist Processes Associated With Changes in the Propagation of the MJO With Increasing CO2. (17th December 2017) - Adames, Ángel F.; Kim, Daehyun; Sobel, Adam H.; Del Genio, Anthony; Wu, Jingbo
Abstract: The processes that lead to changes in the propagation and maintenance of the Madden‐Julian Oscillation (MJO) as a response to increasing CO2 are examined by analyzing moist static energy budget of the MJO in a series of NASA GISS model simulations. It is found changes in MJO propagation is dominated by several key processes. Horizontal moisture advection, a key process for MJO propagation, is found to enhance predominantly due to an increase in the mean horizontal moisture gradients. The terms that determine the strength of the advecting wind anomalies, the MJO horizontal scale and the dry static stability, are found to exhibit opposing trends that largely cancel out. Furthermore, reduced sensitivity of precipitation to changes in column moisture, i.e., a lengthening in the convective moisture adjustment time scale, also opposes enhanced propagation. The dispersion relationship of Adames and Kim, which accounts for all these processes, predicts an acceleration of the MJO at a rate of ∼3.5% K −1, which is consistent with the actual phase speed changes in the simulation. For the processes that contribute to MJO maintenance, it is found that damping by vertical MSE advection is reduced due to the increasing vertical moisture gradient. This weaker damping is nearly canceled by weaker maintenance by cloud‐radiative feedbacks, yielding the growth rate from the linear moisture mode theory nearly unchanged with the warming. Furthermore, the estimated growth rates are found to be a small, negative values, suggesting that the MJO in the simulation is a weakly damped mode. Plain Language Summary: The processes that lead to changes in the propagation of the Madden‐Julian Oscillation (MJO) as a response to increasing CO2 are examined. Based on energy budgets and an existing theoretical framework, we find that four parameters can explain changes in the propagation of the MJO. These are the climatological distribution of moisture, the stability of the tropical atmosphere, the MJO's horizontal scale, and the sensitivity of precipitation to changes in water vapor. When these four processes are considered together they explain the eastward propagation increase of 3.5% K −1 . Key Points: The moisture mode framework of Adames and Kim is used to understand the MJO's response to increasing CO2 in the GISS GCM The moisture mode framework successfully predicts the rate of MJO's phase speed increase with the warming The acceleration of the MJO in a warmer climate is due to the changes in the mean state, moisture‐convection coupling, and the MJO's scale